INTERNET and ICT IMPACT ON ECONOMIC GROWTH - Sulaiman, Hasan; Winata, Andri (Prosiding International conference on Information Technology and Business (ICITB), 2018)
Internet and Information and Communication Technologies (ICT) is an inseparable part of human life today. This paper discusses the impact of the internet and ICT on development and economic growth comes from international journals that discuss about it and of course with a different viewpoint. The research objective was to determine whether the internet and ICT impact on growth and economic development based on international journals and comparing the results of the international journals. The results of the -jurnal journal is that in general the internet and ICT has an impact on economic development and growth of a country. The difference is that the first journal is not only limited to the expansion of the Internet business, but changing the way of doing business; The second journal is ICT is not overly significant effect on economic growth but the effect on the reduction of energy consumption; The third journal is the increasing use of the Internet helped in marketing and communications; The fourth is the internet journals positive impact on economic growth; and fifth journal is the average ICT contribute positively to economic growth. The third journal is the increasing use of the Internet helped in marketing and communications; The fourth is the internet journals positive impact on economic growth; and fifth journal is the average ICT contribute positively to economic growth. The third journal is the increasing use of the Internet helped in marketing and communications; The fourth is the internet journals positive impact on economic growth; and fifth journal is the average ICT contribute positively to economic growth.